2021
DOI: 10.1097/bpo.0000000000001791
|View full text |Cite
|
Sign up to set email alerts
|

Hip Morphology in Early-stage LCPD: Is There an Argument for Anatomic-specific Containment?

Abstract: Background: Early containment surgery has become increasingly popular in Legg-Calvé-Perthes Disease (LCPD), especially for older children. These procedures treat the proximal femur, the acetabulum, or both, and most surgeons endorse the same surgical option regardless of an individual patient's anatomy. This "one-surgery-fits-all" approach fails to consider potential variations in baseline anatomy that may make one option more sensible than another. We sought to describe hip morphology in a large series of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…All radiographic measurements obtained at the initial presentation, 3-month, and 2-year postop visits were performed by 1 of 2 authors, experienced in making these measurements in clinical practice as well as in previous published literature. 11 Previous studies have demonstrated excellent inter-rater reliability for all included radiographic metrics: Waldenström classification (κ: 0.76 to 0.82), NSA (ICC: 0.58 to 0.89), AI (ICC: 0.42 to 0.95), and LCEA (ICC: 0.64 to 0.97). [12][13][14] As such, reliability was not assessed in this study.…”
Section: Radiographic Assessmentmentioning
confidence: 80%
See 1 more Smart Citation
“…All radiographic measurements obtained at the initial presentation, 3-month, and 2-year postop visits were performed by 1 of 2 authors, experienced in making these measurements in clinical practice as well as in previous published literature. 11 Previous studies have demonstrated excellent inter-rater reliability for all included radiographic metrics: Waldenström classification (κ: 0.76 to 0.82), NSA (ICC: 0.58 to 0.89), AI (ICC: 0.42 to 0.95), and LCEA (ICC: 0.64 to 0.97). [12][13][14] As such, reliability was not assessed in this study.…”
Section: Radiographic Assessmentmentioning
confidence: 80%
“…AI was measured as the angle between the line drawn through the superior aspect of the triradiate cartilage bilaterally and a line drawn superolateral triradiate cartilage to the lateral sourcil (weight-bearing aspect of the acetabulum), while LCEA was measured as the angle between the line perpendicular to the line connecting the center of both femoral heads and the line drawn from the center of the femoral head to the lateral most portion of the lateral sourcil. All radiographic measurements obtained at the initial presentation, 3-month, and 2-year postop visits were performed by 1 of 2 authors, experienced in making these measurements in clinical practice as well as in previous published literature 11 . Previous studies have demonstrated excellent inter-rater reliability for all included radiographic metrics: Waldenström classification (κ: 0.76 to 0.82), NSA (ICC: 0.58 to 0.89), AI (ICC: 0.42 to 0.95), and LCEA (ICC: 0.64 to 0.97) 12–14 .…”
Section: Methodsmentioning
confidence: 99%
“…Legg-Calvé-Perthes Disease Selberg et al hypothesized that variable anatomy supports the concept of anatomically specific containment in Legg-Calvé-Perthes disease. Of 168 patients, 35% were substantially dysplastic, 30% were in varus, and 12% were in valgus, suggesting that the one-surgery-fits-all approach may lack specificity for an individual patient 69 .…”
Section: Slipped Capital Femoral Epiphysis (Scfe)mentioning
confidence: 99%
“…We recently read the article by the International Perthes Study Group1 with great enthusiasm as they are attempting to find answers a complex problem. We have a few suggestions for consideration that we believe are relevant to the study.…”
mentioning
confidence: 99%